Alterações metabólicas e morfométricas induzidas por hipóxia em Gallus gallus - Oliveira, Evandro Menezes de [UNESP] (2014)
Two experiments were conducted in order to evaluate whether ingestion of up to 5% of citrus pectin alters the performance, body weight, digestibility of feed and the physical and chemical composition of egg of laying hens. In the first experiment two hundred Lohmann Brown laying hens were used in the 29th to 41th week of age, the body weight evenly distributed (1.70kg ± 0.31kg) in a completely randomized design with five treatments in percentages of soluble fiber diets (control diet without pectin, 2%, 3%, 4% and 5% of purified citrus pectin), with five replicates of eight birds each. The performance and the eggs were analyzed in the total period of the experiment and analyzed for 4 interspersed periods of three weeks (31th, 34th, 37th and 40th weeks of age). The results showed that the performance of birds fed with soluble fiber intake did not affect feed intake, egg production and the egg weight were not changed during the experimental period and consequently the feed conversion was also no affected. The body weight of the birds that ate standard feed without pectin had an increase in weight gain of the 29th to 41st week of age, it was not observed in laying hens fed diets with pectin. Egg weight was increased with feed intake with 3%. The physical and chemical characteristics of the eggs were changed according to the percentage of pectin and age of the birds, and the yolk cholesterol is decreased when the pectin is ingested for up to six weeks. In the second experiment eighty Lohmann Brown hens were used at 37 weeks of age, in with five treatments percentages of soluble fiber in the diet (control diet without pectin, 2%, 3%, 4% and 5% pectin purified citrus), with five replicates of four birds per experimental unit. We analyzed the digestibility of the ration by the method of total excreta collection for 5 days. The results showed that pectin increases the volume and the moisture of excreta and the digestibility ...